2006
DOI: 10.1152/japplphysiol.00943.2005
|View full text |Cite
|
Sign up to set email alerts
|

Delayed threshold for active cutaneous vasodilation in patients with Type 2 diabetes mellitus

Abstract: Delayed threshold for active cutaneous vasodilation in patients with Type 2 diabetes mellitus. J Appl Physiol 100: 637-641, 2006. First published October 6, 2005 doi:10.1152/japplphysiol.00943.2005.-Epidemiological evidence suggests decreased heat tolerance in patients with Type 2 diabetes mellitus (T2DM), but it is not known whether the mechanisms involved in thermoregulatory control of skin blood flow are altered in these patients. We tested the hypothesis that individuals with T2DM have a delayed internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 24 publications
4
47
2
Order By: Relevance
“…51 Another study showed that the internal temperature at which vasodilation took place during passive whole-body heat exposure was higher for people with type 2 diabetes than for healthy individuals. 53 The delayed onset of skin vasodilation was due to a delay in the active vasodilatory response, not to an increase in vasoconstrictor activity.…”
Section: Diabetes Mellitusmentioning
confidence: 98%
“…51 Another study showed that the internal temperature at which vasodilation took place during passive whole-body heat exposure was higher for people with type 2 diabetes than for healthy individuals. 53 The delayed onset of skin vasodilation was due to a delay in the active vasodilatory response, not to an increase in vasoconstrictor activity.…”
Section: Diabetes Mellitusmentioning
confidence: 98%
“…As the incidence and prevalence of T2DM are increasing, also increasing are the number of individuals who are otherwise relatively healthy and live with T2DM but manage it well so that the number of comorbid conditions is minimal. We have therefore focused our efforts on this growing population in our attempts to understand mechanisms of cutaneous microvascular dysfunction in T2DM (12)(13)(14). Recent studies in our laboratory have shown that relatively healthy individuals with T2DM exhibit less nitric oxide-dependent vasodilation during local and whole body thermal stimuli compared with age-matched controls (12,13).…”
mentioning
confidence: 99%
“…SkBF was measured as cutaneous red blood cell flux using Periflux laser-Doppler flowmetry (LDF) as previously described (11,13). One LDF probe (Periflux System 5000; Perimed, Stockholm, Sweden) was attached adhesively to the ventral side of the left forearm in a specialized holder that measures and controls temperature over an area of 12 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior to local warming, baseline data were recorded for 7-10 min while local temperature was held constant at 32°C. Local temperature was then increased to 42°C at a rate of 1°C/s, and held at 42°C for 35 min, as previously described (11,13). Subjects were asked whether they felt any pain or discomfort during the local warming; no subject reported feeling any pain or discomfort.…”
Section: Methodsmentioning
confidence: 99%